Music improves the therapeutic effects of bevacizumab in rats with glioblastoma: Modulation of drug distribution to the brain - Semyachkina-Glushkovskaya, Oxana; Diduk, Sergey; Anna, Eroshova; Elina, Dosadina; Artem, Kruglov; Khorovodov, Alexander; Shirokov, Alexander; Fedosov, Ivan; Dubrovsky, Alexander; Blokhina, Inna; Terskov, Andrey; Navolokin, Nikita; et al. (Frontiers in Oncology, 2022)
Background: The development of new methods for modulation of drug distribution across to the brain is a crucial step in the effective therapies for glioblastoma (GBM). In our previous work, we discovered the phenomenon of music-induced opening of the blood-brain barrier (OBBB) in healthy rodents. In this pilot study on rats, we clearly demonstrate that music-induced BBB opening improves the therapeutic effects of bevacizumab (BZM) in rats with GBM via increasing BZM distribution to the brain along the cerebral vessels. Methods: The experiments were performed on Wistar male rats using transfected C6-TagRFP cell line and the loud rock music for OBBB. The OBBB was assessed by spectrofluorometric assay of Evans Blue (EB) extravasation and confocal imaging of fluorescent BZM (fBZM) delivery into the brain. Additionally, distribution of fBZM and Omniscan in the brain was studied using fluorescent and magnetic resonance imaging (MRI), respectively. To analyze the therapeutic effects of BZM on the GBM growth in rats without and with OBBB, the GBM volume (MRI scans) as well as immunohistochemistry assay of proliferation (Ki67 marker) and apoptosis (Bax marker) in the GBM cells were studied. Results: Our finding clearly demonstrates that music-induced OBBB increases the delivery of EB into the brain tissues and the extravasation of BZM into the brain around the cerebral vessels of rats with GBM. Music significantly increases distribution of tracers (fBZM and Omniscan) in the rat brain through the pathways of brain drainage system (perivascular and lymphatic), which are an important route of drug delivery into the brain. The music-induced OBBB improves the suppressive effects of BZM on the GBM volume and the cellular mechanisms of tumor progression that was accompanied by higher survival among rats in the GBM+BZM+Music group vs. other groups. Conclusion: We hypothesized that music improves the therapeutic effects of BZM via OBBB in the normal cerebral vessels and lymphatic drainage of the brain tissues. This contributes better distribution of BZM in the brain fluids and among the normal cerebral vessels, which are used by GBM for invasion and co-opt existing vessels as a satellite tumor form.